Strategies for motivating embryology learning: an experience report in the nursing course of the Federal University of Rio Grande do Sul - Marcuzzo, Simone; Campos, Paola Melo; Schneider, Júlia; Régis, Claudenilson da Costa (Universidade Estadual de Campinas, 2019)
The behavior of the student in Higher Education in relation to their learning process is a question often discussed. The beginning of the curricula in the health area are theoretical and in the biological area, which can lead in demotivation to the learning in the freshmen. The present report aims to present the experience of the use of active methodologies in the Nursing course in order to make the learning of Embryology more meaningful. This action research hadas objectives: relate basic theoretical contents with the disciplinary practices and involve the attention of the student with the content developed in the classroom. The approach of the theory with the professional practice was obtained by means ofthe participation of monitors in the seminars presented by the students. The monitors contributed with reports of practical experiences, verifying the importance of the theory. Videos, diagrams, mock-ups, practical classes and study guides were the strategies used to deal with the content, contrasting the traditional model of expository class. An extra class space in social network was created, which allowed the sharing of supplementary material to the classes. We evaluate this action research through by means of the application of an instrument with closed questions, associated with students' reports. We found that the participation of the classroom monitors assisted the contextualization of the importance of Embryology for Nursing professionals. Through the comments of the students, it was observed that the introduction of varied didactic strategies provided greater participation and motivation.